Investigating salience strategies to counteract obesity. (18th February 2021) - Pinero de Plaza, Maria Alejandra; Taghian, Mehdi; Marmolejo-Ramos, Fernando; Barrera-Causil, Carlos J; Hall, John
Summary: The investigation of the characteristics and attributes that make a brand prominent for shoppers is known as salience research. This line of study concentrates on influencing buying behaviors via the manipulation of shopping environments and food products. Such promotional strategies successfully attract massive food sales and therefore have been associated with changes in dietary patterns and the epidemic expansion of non-communicable diseases, like obesity. Marketers have empirically proven that global buying patterns are influenced by their salience strategies and techniques. However, despite the significance of such methods, empirical salience investigations have rarely been extended beyond their primary business focus to the field of health promotion. Therefore, this study is presenting a way of transferring the salience knowledge to the health promotion field in order to track dietary choices and possibly gain information to identify buying and eating behaviors connected to obesity. The salience literature from various disciplines permits to hypothesize that consumers are more likely to have unhealthy diets when food-choices and conditions are saliently manipulated. A quasi-experimental method (combining salience measures with Bayesian analysis) was used to test this proposition. The results support the hypothesis and endorse the introduced research tool. As predicted, data reflect the latest national overweight and obesity statistics and suggest that habitual unhealthy diets are more likely when salience strategies link food products to taste, social and emotional attributes. These preliminary findings encourage further investigation to enhance the method as a possible epidemiological tool.